An AGV scheduling and routing system for high-throughput container handling - Yu, Xin Guo. (2009)
It is very likely that AGVs(Automated Guided Vehicles) will be used in the high throughput container ports, such as Singapore Port and Hong Kong Port. AGV systems are the most economical way of moving material. It is designed to interface with other systems, such as the berth planning systems so that the whole operation of the port can be automated. Therefore, it is very important to design a safe and efficient AGV system. To operate safely and efficiently, an AGV system has to solve issues like collisions, congestions, deadlocks and livelocks. Up to now, decentralized approaches to control AGVs are able to reduce the probability of these situations, but not able to produce a system which is free of them.